Peningkatan Kemampuan Membaca Peserta Didik dengan Menggunakan Media Komik - Indana Zulfa; Ibnu Muthi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The ability to read with comprehension is a fundamental skill that is very crucial for children in elementary school. However, many students face challenges due to lack of interest in reading and teaching methods that feel monotonous. The purpose of this study is to evaluate how effective comic media is in improving students' reading comprehension. Using a literature review approach through a qualitative descriptive method, this study explores relevant literature on comic media, educational theory, and reading ability. The findings of the study indicate that comics, which combine text elements with visuals, can attract students' attention, make it easier for them to understand reading, and create a fun and interactive learning atmosphere. In addition, comics are also in accordance with the characteristics of elementary school children who tend to have visual interests and require relevant learning media. With the right usage strategy, comic media can function as an innovative alternative in teaching Indonesian to improve students' literacy skills from the start.